2006
DOI: 10.1007/s00113-006-1140-3
|View full text |Cite
|
Sign up to set email alerts
|

Die intermittierende Impulskompression zur Abschwellung und Thromboseprophylaxe – Pilotstudie nach Hüft-TEP

Abstract: These preliminary results suggest that pump systems can prevent deep venous thrombosis after hip surgery even when applied for only short intervals over a short period of time. However, large scale confirmatory studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Using the AVI system, Gardner and Fox demonstrated a positive effect on the microcirculatory physiology of the leg [5,23]. Several clinical studies have demonstrated the effectiveness of intermittent impulse compression in cases of skeletal trauma and total hip replacement, both as a stand-alone procedure or in synergy with heparin (add-on therapy) [8,10,11,[16][17][18]21].…”
Section: Introductionmentioning
confidence: 99%
“…Using the AVI system, Gardner and Fox demonstrated a positive effect on the microcirculatory physiology of the leg [5,23]. Several clinical studies have demonstrated the effectiveness of intermittent impulse compression in cases of skeletal trauma and total hip replacement, both as a stand-alone procedure or in synergy with heparin (add-on therapy) [8,10,11,[16][17][18]21].…”
Section: Introductionmentioning
confidence: 99%